A global hybrid derivative-free method for high-dimensional systems of nonlinear equations - Begiato, Rodolfo G. (2021)
Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) under the projects PTDC/MAT-APL/28400/2017 and UID/MAT/00297/2019. Marcia A. Gomes-Ruggiero: Partially supported by PRONEX-Optimization; CNPq (Grants 306220/2009-1 and 309733/2013-8); FAPESP (Grants 2013/05475-7 and 2013/07375-0) and CAPES.